Kabir: selected sakhis : the vision of wisdom - Sinha, Chandan (New Delhi Rupa, 2020)
The Bhakti saint-poet Kabir$1 (Bs sakhis or couplets are expressions of his love for God, his insights into the principles for living a good life and signposts on the simple path to the Almighty. Popular for over five hundred years, these dohas are Kabir$1 (Bs conversations with God, with himself and with us in everyday but colourful tongue that leave their mark on readers of all ages. They speak to us of God, humility, truth, maya and much more.s
Keywords: Kabir; Religions